Ventilation for Residential Buildings: Critical Assessment of Standard Requirements in the COVID-19 Pandemic Context - Aguilera Benito, Patricia; Piña Ramírez, Carolina; Viccione, Giacomo; Lepore, Ester (Frontiers in Built Environment, 2021)
After the arrival of a new airborne virus to the world, science is aiming to develop solutions to withstand the spread and contagion of SARS-CoV-2. The most severe among the adopted measures is to remain in home isolation for a significant number of hours per day, to avoid the spreading of the infection in an uncontrolled way through public spaces. Recent literature showed that the primary route of transmission is via aerosols, especially produced in poorly ventilated inner spaces. Spain has reached very high levels concerning contagion rates, accumulated incidence, or number of hospitalizations due to COVID-19. Therefore, this article aims to develop a quantitative and qualitative analysis of the requirements established in Spain, with respect to the European framework in reference to ventilation parameters indoors. The different parameters that serve as calculation for the ventilation flow in homes are analyzed to this aim. Results show that the criteria established in the applicable regulations are insufficient to ensure health and avoid contagion by aerosols indoors.